Why A Few? And Why Not *A Many? - Solt, Stephanie D. (Proceedings of Sinn und Bedeutung, 2019)
The expressions few and a few are typically considered to be separate quantifiers. I challenge this assumption, showing that with the appropriate definition of few, a few can be derived compositionally as a + few. The core of the analysis is a proposal that few has a denotation as a one-place predicate which incorporates a negation operator. From this, argument interpretations can be derived for expressions such as few students and a few students, differing only in the scope of negation. I show that this approach adequately captures the interpretive differences between few and a few. I further show that other such pairs are blocked by a constraint against the vacuous application of a.